The Chemical Composition of Grapes: Constituents, Measurement Methods, and Nutritional-Biological Significance - Mamurov, Murodjon (American Journal of Biodiversity, 2025)
The article provides a systematic analysis of the chemical composition of grape (Vitis vinifera L.) fruit. It highlights the major constituent groups, including water, carbohydrates (glucose, fructose), organic acids (primarily tartaric and malic acids), phenolic compounds (flavonoids, anthocyanins, tannins), nitrogenous components (free amino acids, proteins), pectin and fibers, mineral elements (K, Ca, Mg, etc.), vitamins (C, K, B group), as well as volatile aromatic compounds (monoterpenes, norisoprenoids, esters). The application areas of modern analytical methods such as refractometry, titration, HPLC/UPLC, UV-Vis, GC-MS, ICP-OES/ICP-MS are discussed. Based on the literature, the effects of range indicators, variety, ripening stage, agro-climate, and storage/juicing processes on composition are examined. The conclusions drawn from this analysis have practical significance for grape product quality management and the development of strategies for utilizing functional foods and biopotentials.